Significación del Inti Raymi en la Cosmovisión Andina de la Parroquia de Cacha periodo 2022 - Pérez Romero, Evelyn Anabel (2025)
The Inti Raymi or better known as the festival of the sun takes place every June 21 of each year in the parish of Cacha, Chimborazo Province, it is an ancient festival that seeks to thank Pachamama. They celebrate to strengthen the relationship with the soil and agricultural production, to bless the food received from the green fields and golden wheat fields; this festival is characterized by music and traditions all aimed at promoting new production for the community and greatly influences the Andean worldview of the inhabitants of this area, such as carrying out certain activities at the right time and day because if they do not do so they would not have a good result for their spirit, the ritual encompasses more of the spiritual, which has currently been lost in modernization. The loss of this custom is directly related to the evolution of the people, where the new generations do not have a direct link with their roots, leaving aside their traditions affecting the legacy of their ancestors, due to the poverty that is experienced in the rural sector forcing them to migrate to the big cities in search of a better future in the economic and social field, this festivity is part of the identity of the indigenous people, which involves their Andean worldview and the documentation that is intended to be carried out will present us with the opportunity to spread their knowledge, beliefs and culture to new generations so that the rituals of their ancestors remain alive.